Medical decision making - Sox, Harold C.; Higgins, Michael C. (Michael Clark), 1950-; Owens, Douglas K. (Chichester, West Sussex, UK : Hoboken, New Jersey : John Wiley & Sons, 2013)
"This title provides a thorough understanding of the key decision making infrastructure of clinical practice and retains its emphasis on practice and principles of individualized medical decision making"--Provided by publisher.
Differential diagnosis -- Probability: quantifying uncertainty -- Understanding new information: Bayes' Theorem -- Measuring the accuracy of diagnostic information -- Expected value decision analysis -- Markov models and time-varying outcomes -- Measuring the outcome of care-expected utility analysis -- Selection and interpretation of diagnostic tests -- Cost-effectiveness analysis and cost-benefit analysis -- Medical decision analysis in practice: advanced methods.
Rev. ed. of: Medical decision making / Harold C. Sox, Jr. ... [et al.]. c1998.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Diagnosis, Differential; Cost-Benefit Analysis; Decision Making; Probability; MEDICAL / Diagnosis; MEDICAL / Laboratory Medicine; MEDICAL / Nursing / Assessment & Diagnosis; Diagnosis, Differential; Cost effectiveness; Decision making; Probabilities; Cost effectiveness; Decision making; Diagnosis, Differential; Probabilities; Electronic books; E-books.; Downloadable e-books.